LncRNA CKMT2-AS1 Promotes Hepatocellular Carcinoma Development Via Sponging miR-142-5p and Targeting IFITM3 - Ding, Xiaobo; Jiao, Chengming; Zou, Yitian; Han, Zheng; Liu, Shengjin (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Hepatocellular carcinoma (HCC) stands as the foremost contributor to cancer-related mortality, underscoring its profound significance in the oncological landscape. This study explores the potential regulatory mechanisms of lncRNA CKMT2-AS1 in the functionality of HCC cells, thereby providing a basis for therapeutic approaches in the treatment of HCC. Materials and Methods: Quantitative polymerase chain reaction (qPCR) was utilized to evaluate the expression of CKMT2-AS1 and miR-142-5p in HCC tissues and cells. The interactions between CKMT2-AS1 and miR-142-5p, as well as the interplay between IFITM3 and miR-142-5p, were confirmed through dual-luciferase assays. To assess the effects of CKMT2-AS1 transfection, alongside the co transfection of CKMT2-AS1 and miR-142-5p interference plasmids, a series of experiments were conducted utilizing CCK-8 and tran swell assays to evaluate changes in proliferation, migration, and invasion of HCC cells. Additionally, qPCR was employed to elucidate the influence of miR-142-5p on the expression of IFITM3 in HCC cells. Results: The study elucidated that CKMT2-AS1 was significantly upregulated in HCC tissues and cells, while miR-142-5p exhibited a marked downregulation, revealing a noteworthy negative correlation. Notably, the downregulation of CKMT2-AS1 hindered the function of HCC cells. Conversely, the downregulation of miR-142-5p effectively mitigated the inhibitory effects of CKMT2-AS1 on cellular activi ties. Furthermore, the upregulation of miR-142-5p resulted in a substantial decrease in the levels of IFITM3 in HCC cells. This investiga tion established a potential regulatory network, identifying IFITM3 as the downstream target mRNA. Conclusion: The sponging effect of CKMT2-AS1 on miR-142-5p resulted in altered expression levels of IFITM3, subsequently influencing the progression of HCC. Cite this article as: Ding X, Jiao C, Zou Y, Han Z, Liu S. LncRNA CKMT2-AS1 promotes hepatocellular carcinoma development via sponging miR-142-5p and targeting IFITM3. Turk J Gastroenterol. 2025;36(11):776-786.